2021
DOI: 10.1371/journal.pone.0246959
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-transport diet, transport duration and transport condition on immune cell subsets, haptoglobin, cortisol and bilirubin in young veal calves

Abstract: The aim of this study was to investigate effects of pre-transport diets, transport durations and transport conditions on immune cell subsets, haptoglobin, cortisol and bilirubin of young calves upon arrival at the veal farm. An experiment was conducted with a 2 × 2 × 2 factorial arrangement with 3 factors: 1) provision of rearing milk or electrolytes at the collection center (CC); 2) transport duration (6 or 18 hours) and 3) transport condition (open truck or conditioned truck). Holstein-Friesian and cross-bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…There are few studies reporting the effect of the diet on this parameter, and no study concerns the integration of olive by-products. It is known that, in cattle, a negative energy balance affects fat mobilization and liver function, leading to an increase in TBIL serum concentrations (Mayasari et al, 2019;Marcato et al, 2021;Hisadomi et al, 2022). It has been observed that unsaturated fatty acids, largely present in the OC, reduce bilirubin conjugation, thus increasing its serum concentration (Hargreaves, 1973;Oliveira et al, 2021).…”
Section: Total Bilirubinmentioning
confidence: 99%
“…There are few studies reporting the effect of the diet on this parameter, and no study concerns the integration of olive by-products. It is known that, in cattle, a negative energy balance affects fat mobilization and liver function, leading to an increase in TBIL serum concentrations (Mayasari et al, 2019;Marcato et al, 2021;Hisadomi et al, 2022). It has been observed that unsaturated fatty acids, largely present in the OC, reduce bilirubin conjugation, thus increasing its serum concentration (Hargreaves, 1973;Oliveira et al, 2021).…”
Section: Total Bilirubinmentioning
confidence: 99%
“…In the Netherlands, male (and surplus female) calves born on dairy farms are transported at a minimum age of 14 d, first to a collection center and then to a veal farm (Marcato et al, 2018). Effects of transport on calf physiology and health have been previously documented (e.g., Knowles et al, 1999;Masmeijer et al, 2019;Marcato et al, 2020aMarcato et al, ,b, 2021. Recent observational studies have found associations between the background and rearing practices at the dairy farm of origin and mortality rate of calves at the veal farm (Winder et al, 2016;Renaud et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Whilst legislation aims to control variations between journeys by enforcing transport and feeding regimes, age, and health of the animal, uncontrolled factors are also at play, inter alia , prevailing weather, handling at loading and unloading, delays, driver experience, position within a truck, and parked position on the ferry (exposed or sheltered). Previous studies have also reported that using a conditioned versus an open truck influenced immune cell subsets ( 43 ), but calves transported in summer and winter showed little difference in clinical variables after a 19-h journey ( 16 ). Calves with a low body weight were shown to respond to transport differently than calves that had a normal body weight and similar age ( 17 ).…”
Section: Discussionmentioning
confidence: 99%